Interocular Contrast Balancing Partially Improves Stereoacuity in Keratoconus. Issue 4 (27th April 2023) - Marella, Bhagya Lakshmi; Vaddavalli, Pravin Krishna; Reddy, Jagadesh C.; Conway, Miriam L.; Suttle, Catherine M.; Bharadwaj, Shrikant R.
Abstract : SIGNIFICANCE: Partial improvement in stereoacuity may be achieved by balancing the contrast input to the two eyes of patients with bilaterally asymmetric keratoconus. PURPOSE: Interocular differences in image quality, characterized by dissimilar contrast loss and phase shifts, are implicated in stereoacuity loss in keratoconus. This study determined whether contrast balancing improves stereoacuity in this disease condition and, if so, whether it is dependent on the baseline interocular contrast imbalance. METHODS: Interocular contrast imbalance and stereoacuity of 43 subjects (16 to 33 years) with bilaterally asymmetric keratoconus were tested with spectacle correction as baseline using a binocular rivalry paradigm and random-dot stereograms, respectively. Stereoacuity measurements were repeated in a subset of 33 subjects at their contrast balance point (i.e., contrast level in stronger eye allowing balanced rivalry with 100% contrast in weaker eye) and with contrast levels biased in favor of stronger or weaker eye, all conditions in randomized order. RESULTS: Contrast imbalance level was significantly correlated with the subject's stereoacuity at baseline ( r = −0.47, P = .002). The median (25th to 75th interquartile range) stereoacuity improved by 34.6% (19.0 to 65.1%) from baseline (748.8 arc sec [261.3 to 1257.3 arc sec]) to the contrast balanced condition (419.0 arc sec [86.6 to 868.9 arc sec]) ( P < .001), independent of their baseline stereoacuity or contrast imbalance levels ( r < 0.2, P > .26 for both). Contrast bias in favor of the weaker eye (881.3 arc sec [239.6 to 1707.6 arc sec]) worsened stereoacuity more than a bias toward the stronger eye (502.6 arc sec [181.9 to 1161.4 arc sec]), both relative to the contrast balanced condition ( P < .002). CONCLUSIONS: Interocular contrast balancing partially improves stereoacuity in bilaterally asymmetric keratoconus, independent of their baseline contrast imbalance level. Cyclopean viewing may be inherently biased toward the input from the stronger eye in keratoconus.